Politik Kekerabatan dan Kualitas Kandidat di Sulawesi Selatan - Purwaningsih, Titin (Jurnal Politik, 2015)
This paper aims to elaborate the increase of political kinship phenomenon in South Sulawesi, especially from the perspective of political legacy of a candidate from parti¬cular political family. Utilizing a qualitative research method, the paper reveals that in kinship politics, interest in politics is transferred through political discussions within family, activities in political parties and social organizations. There is also process of transferring networks and family brands that will help a candidate to gain public sup¬ports. This paper also reveals that direct elections of local leaders and majority votes of proportional open list election system open more opportunities for political family to increase more power as family members are being elected in political leaderships. However, the quality of candidates tends to decrease as shown by relatively younger candidates with less political experience. The new political parties and the lack of re¬generation provide opportunities for the members of political family to gain power in their early age. This paper suggests that the quality of candidate is an important feature of kinship politics which will enrich the previous studies in the characteristics of kinship politics as argued by Hess, Casey, Asako as well as Dal Bo and Querobin.